RUMAH ADAT â€œTONGKONANâ€ ORANG TORAJA KABUPATEN TANA TORAJA PROPINSI SULAWESI SELATAN - Pakan, Marcelina Sanda Lebang; Pratiknjo, Maria Heny; Mamosey, Welly E. (Universitas Sam Ratulangi, 2018)
The Toraja people create a House that is not separated from the State of the economy apart from the family, but that, too, there are still other factors that determine the shape of their home i.e. level socio. They know there are three levels of social layer i.e. the aristocracy occupied a high status in society, the middle class is called to makaka independent i.e. not controlled by the nobility, and the earthy i.e. they called kaunan equivalent of slave society. The House of independence that makes custom homes and occupy Tongkonan.Custom homes called Tongkonan houses gathered i.e. Regent custom to sit with military duty. Tongkonan houses there are three kinds in accordance with its function before entering a new Government system to Tana Toraja by Netherlands East Indies Government namely Tongkonan Layuk functions as the center of custom events, and drafting Community rules also place Center of religious activities, Tongkonan Keparangngesan functions as a Center for the implementation of customs and customs violations sanctions that occur in society. Tongkonan Paparuan functions as the central activity of the family members of the owner's Tongkonan perceived like a wedding ceremony, a Thanksgiving, as well as the place of execution of the funerals of the dead.The third function of the Tongkonan above this has undergone a change with the influx of Netherlands Indies government system so that all the Affairs of indigenous power diahlikan to the new pemrintahan system. Also the inclusion of the Gospel by the missionary Agency Zending Netherlands Netherlands from the land in the early 20th century (1912) concerns the religious ceremony so that redirected to the belief system of Christianity..Keywords: tongkonan, House, Toraja